Abdul Karim Soroush: Pluralism and Religious Freedom - Tyas Setyanti; Shofiyullah Muzammil (al-Afkar, Journal For Islamic Studies, 2026)
The debate on pluralism and religious freedom remains a hot topic of discussion today. There are pros and cons to both schools of thought. Abdulkarim Soroush, a reformer who actively advocates pluralism and religious freedom, aims to understand Soroush's thoughts on pluralism and religious freedom. This study uses a descriptive qualitative methodology with a historical-critical approach. The results of this study are Soroush's thoughts on the dynamics of religious knowledge that lead to the concepts of pluralism and religious freedom. According to Soroush, plurality is the norm in this world. There is nothing wrong with recognizing the same plurality (species) in the world of religions. Religious freedom has been taught by the prophets (including the Prophet Muhammad), namely never forcing individuals to believe, spreading goodness and truth. Therefore, Islam in particular cannot prevent its followers from choosing a religion freely and consciously, ignoring the dynamism of religious freedom.